2009
DOI: 10.1007/s10029-009-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Giant perineal hernia: laparoscopic mesh repair complemented by a perineal cutaneous approach

Abstract: Symptomatic perineal herniation after abdominoperineal resection is a rare complication and its management remains challenging. Perineal laparoscopic mesh repair is safe and effective and can be performed with minimal complications. We report a giant perineal hernia treated by a combined laparoscopic mesh repair approach and plastic resection of the cutaneous perineal wound. To the best of our knowledge, this is the first report with this technical approach that we could find in the English literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
5
0
3
Order By: Relevance
“…Gomez Portila et al have confirmed that proper mesh fixation considerably decreases recurrence when the mesh can be implanted successfully in the absence of pelvic floor infection [3]. Still, there are studies reporting recurrence rates as high as 16% [8].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Gomez Portila et al have confirmed that proper mesh fixation considerably decreases recurrence when the mesh can be implanted successfully in the absence of pelvic floor infection [3]. Still, there are studies reporting recurrence rates as high as 16% [8].…”
Section: Discussionmentioning
confidence: 96%
“…During the intervention a biological implant (Permacol) was styled to the perineal defect and the residual perineal facia was closed with interrupted 2-0 absorbable sutures [6]. In another case a giant perineal hernia was repaired using a combined approach of laparoscopic mesh repair and plastic resection of the cutaneous perineal wound [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebenso werden verschiedene Materialien zur Defektdeckung genutzt, wie permanente prosthetische Netze oder autologisches Gewebe mit möglicher Deckung durch muskulokutane Verschiebelappen. Jede Technik weist Vor-und Nachteile auf, die individuell gegeneinander abgewogen werden müssen [3,4].…”
Section: Introductionunclassified
“…Dem gegenüber stehen die Risiken einer Bauchöffnung wie Infektionen bis hin zur Peritonitis, Verwachsungen, Blutungen oder Verletzungen anderer Organe. Der laparoskopische Zugang, der bei einigen Patienten in der englischsprachigen Literatur gewählt wurde [4,5], minimiert derartige Risiken. Akatsu …”
Section: Introductionunclassified